The dynamic interdependencies among the negativity and the positivity in news and user-generated content about safety in a firm's products and the firm's product recalls. - Vivek Astvansh; Yen-Yao Wang (PLoS ONE)
This article examines the dynamic interdependencies among the negativity and the positivity in news and user-generated content about safety in a firm's products (or the lack thereof) and the firm's product recalls. The authors use a panel vector autoregression (PVAR) to unearth theoretically novel and managerially relevant asymmetric associations. Specifically, they find that the negativity in the news negatively correlates with recalls, whereas the negativity in UGC positively correlates with recalls. Whereas the positivity in the news positively correlates with recalls, the positivity in UGC does not matter. Further, the negativity in the news and the negativity in UGC substitute for each other, whereas their positive counterparts complement each other's associations with recalls. Lastly, the negativity and positivity in the news have significant, though differently patterned, long-term associations with recalls. The findings contribute to research on the associations between earned media and managerial decisions in the product market.